Effects on relaxation properties of Chinese cabbage (Brassica campestris L.) subjected to different compression directions. (July 2021) - Zhang, Jing; Wang, Jun; Hao, Yifeng; Zheng, Chengyu; Du, Dongdong
Abstract : Relaxation tests were performed to determine the viscoelastic properties of intact Chinese cabbage under transverse and longitudinal loading using Maxwell models. The differences in the relaxation properties for different compression directions were evaluated and a variety of macroscopic deformation characteristics was described using a stereomicroscope. It was found that Chinese cabbage showed rheological properties and elasticity under low loading speed and small deformations, and the upper limit value of failure and deformation in transverse compression was greater than that for longitudinal compression. Additionally, relaxation rate in the transverse loading process was generally faster than that in the longitudinal process, and resistance to deformation and viscosity during the transverse loading process was stronger than that in the longitudinal process. This suggested that the relaxation parameters of cabbages greatly differed in different locations, and the loading directions seem to affect the Maxwell model parameters and peak force response. This is probably because of the differences in cell tissue structure and arrangement which changed in the intercellular space during the loading process. Moreover, the differences in relaxation behaviours under different loading directions could be explained by the micro-mechanical properties of their tissue's cell structure, which is consistent with the evaluation results of the relaxation rate. The precise description of the differences in rheological properties of Chinese cabbage under different loading directions could help optimise the packaging and storage strategies and determine the most appropriate process parameters to reduce mechanical damage during storage and processing operations. Highlights: Rheological properties and elasticity are important parameters for Chinese cabbage. Relaxation behaviour could be effectively described by four-element Maxwell model. Differences existed in the relaxation process for two different loading methods. Macro-mechanical properties of cabbage were closely related to micro-mechanical properties.